Functional polymorphisms of the receptor for the advanced glycation end product promoter gene in inflammatory bowel disease: a case-control study - Ciccocioppo, Rachele; Bozzini, Sara; Betti, Elena; Imbesi, Venerina; Klersy, Catherine; Lakyova, Lucia Sukovska; Sukovsky, Lukas; Benacka, Jozef; Kruzliak, Peter; Corazza, Gino Roberto; Di Sabatino, Antonio; Falcone, Colomba (Clinical and Experimental Medicine, 2019)
The receptor for the advanced glycation end products (RAGE) is a multiligand transmembrane receptor involved in chronic inflammation whose specific polymorphisms of the promoter gene were found to increase its transcriptional activity. We investigated the association of both allelic and genotypic -374T/A and -429T/C polymorphisms with inflammatory bowel disease. The STREGA guidelines were applied for planning and reporting. We enrolled 133 patients with Crohn's disease (CD), 149 with ulcerative colitis (UC), and 128 blood donors. Genomic DNA was extracted from peripheral blood leukocytes collected from each patient and control. RAGE polymorphisms were analyzed by PCR-restriction fragment length polymorphism assay. The Hardy-Weinberg equilibrium was first assessed, and then, the Kruskal-Wallis test and the Fisher exact test were used for etiologic group comparisons. Distribution of patients' characteristics across genotypes was evaluated by the Fisher exact test, while that across alleles was analyzed with a probit model. A 2-sided value of p < 0.05 was considered significant. Following the evidence of the Hardy-Weinberg equilibrium, we found a higher prevalence of the allele A of the -374T/A haplotype in UC (p = 0.043), and of the allele C of the -429T/C haplotype in CD (p < 0.001) with respect to the other groups. Moreover, the homozygous AA genotype of the -374T/A polymorphism resulted associated with late onset of CD, while its TT genotype with early onset (p = 0.049). The allele C of the 429T/C haplotype was associated with early onset of UC (p = 0.03), while a higher frequency of the heterozygous TC haplotype was found in those with pancolitis (p = 0.026). The differing distribution of these polymorphisms in healthy donors and CD/UC patients suggests a role in the development and outcome of these pathological conditions.
Keywords: dospělí; Receptor for Advanced Glycation End Products; Genotype; Female; Prevalence; Adult; polymorfismus délky restrikčních fragmentů; mladý dospělý; ženské pohlaví; jednonukleotidový polymorfismus; Inflammatory Bowel Diseases; Gene Frequency; lidé; Polymorphism, Single Nucleotide; genotyp; genetická predispozice k nemoci; studie případů a kontrol; Genetic Predisposition to Disease; frekvence genu; Polymorphism, Restriction Fragment Length; prevalence; Male; Case-Control Studies; Young Adult; Genotyping Techniques; genotypizační techniky; idiopatické střevní záněty; lidé středního věku; promotorové oblasti (genetika); mužské pohlaví; receptor pro konečné produkty pokročilé glykace; Promoter Regions, Genetic; Middle Aged; Humans